Daylighting in Urban Context - Bhattacharjee, P; Moitra, S; Mondal, S; Ghosh, K (International Journal of Computer Sciences and Engineering, 2025)
Daylight is the combination of all direct and indirect sunlight during the daytime. This includes direct sunlight, diffuse sky radiation, and (often) both of these reflected by the Earth and terrestrial objects. The penetration of Daylight in the building is not only important for energy conservation context, but also for health and hygiene of the residents. This study has suggested a guideline of access spaces between the different urban buildings. The simulation was done on the Ecotect Analysis software& DIALux lighting software. The different height of the buildings which is considered are 8ft, 15ft, 39ft & 87ft. The dates which are fixed for the experiment were 21st March, 21St June, 22nd September & 21st December. The simulation is done on 8:00 AM, 12:00PM & 4:00PM. The proposed method can greatly assist in improving the urban lifestyle of the people. The results if implemented in a correct way can save some amount of space and the penetration of correct amount of sunlight can be calculated.